Enhanced thermoelectric power generation performance of mixed-phase FeS/FeS2 nanostructures by controlling the reaction time duration. Issue 1 (1st January 2023) - Rehman, Ubaid ur; Mahmood, Khalid; Kamran, Muhammad Arshad; Mohammed, Rawaa M.; Somaily, H.H.; Ashfaq, Arslan; Gul, Qeemat; Ali, Adnan; Iqbal, Muhammad Faisal; Sahar, Kashaf ul
Abstract: Thermoelectric materials can convert heat energy into electricity and could be the future of sustainable energy demand. In the current work, we have successfully improved the thermoelectric performance of hydrothermally synthesized mixed-phase pyrite nanostructures. For this, samples with different FeS/FeS2 phase ratios were synthesized by controlling the reaction time duration. XRD data confirms the formation of mixed phases of FeS and FeS2, which increases with the increase in reaction time, while the Raman spectroscopy results verify the argument. Scanning electron microscope images represents the formation of nanoporous morphology. For thermoelectric properties, both the Seebeck coefficient (44–69 μV/ ° C) and electrical conductivity (33–48 S/cm) were found to be improved with the increase in reaction time (12–48h). This simultaneous enhancement in Seebeck coefficient and electrical conductivity was associated with the energy filtering effect at the crystal interface leading to the improvement in thermoelectric power factor to 2.28 × 10 −5 Wm −1 C −2 (at 25 o C) for 48h sample. Highlights: Mixed-phase FeS/FeS2 samples have been successfully synthesized by the hydrothermal method by varying reaction time duration. Seebeck coefficient and electrical conductivity were improved with the increase in reaction time duration. The improvement in thermoelectric transport parameters was associated with the energy filtering at the crystal interface boundary. The highest power factor∼2.28 × 10 −5 Wm −1 C −2 was achieved for the sample processed at 48h.